SEXISM AND FRIENDSHIP BELIEFS AT MID-LIFE AND BEYOND. (11th November 2018) - Camardo, S; Rieger, T; Mehta, C
Abstract: The homosocial norm is the belief that friendships should occur exclusively between people of the same gender (Monsour, 2002: Rose, 1985). The homosocial norm posits that heterosexuality is viewed as normative and as such, cross-gender friendships are viewed with suspicion and disapproval (Savin-Williams, 2005). Homosocial tendencies have been associated with sexism in adolescence (Keener, Mehta, & Strough, 2013), however little is known about the homosocial norm and sexism in older adulthood. In the current study we investigated associations between the homosocial norm and sexism in a sample of 203 (45 men) adults aged 50–92. Based on research with adolescents, we hypothesized that benevolent and hostile sexism would be positively associated with the homosocial norm for men, and negatively associated with the homosocial norm for women. Our hypothesis was partially supported. Specifically, we found that endorsement of the homosocial norm was positively associated with benevolent (r = .35, p =.02) and hostile sexism (r = .39, p =.009) for men. The homosocial norm was also positively associated with benevolent (r = .35, p <.001) and hostile sexism (r = .31, p <.001) for women. That the endorsement of the homosocial norm was associated with sexism for both older adult men and women may reflect a wider world view and beliefs about traditional roles and behaviors for men and women.